Effect of Mixed Traffic on Capacity of Two-Lane Roads: Case Study on Indian Highways. (2017) - Roy, Nabanita; Roy, Rupali; Talukdar, Hitesh; Saha, Pritam
Abstract: This paper focuses on effects of mixed traffic on capacity of two-lane roads. On the basis of field data collected on Indian highways, the present paper makes it clear that capacity reduces if the proportion of slower vehicles increases in the traffic stream. Since such vehicles are responsible for the formation of platoons, their increasing proportion in traffic would accordingly increase the equivalency factor of vehicles, thereby, resulting in variation in capacity. The present study therefore explicates the need of introducing the concept of dynamic passenger car unit and anticipates that this would alleviate the current implication on capacity standards of such roads under mixed traffic.